ANALISIS STRATEGI PENGEMBANGAN KULINER DALAM PRESPEKTIF ISLAM - Dewi Jayanti (AL-BAYAN: JURNAL HUKUM DAN EKONOMI ISLAM, 2022)
Business is an organized business activity to achieve profit or selling goods and services in order to fullfil society’s need. Due to current development and also changes in the lifestyle, it will lead to changing the human needs, especially primary needs in foods and drinks.If the need for food increases, it will certainly bring business opportunities that can be done by the community. For instance, instant foods and beverages provider. As the results of the study, it can be concluded that a business development strategy that has been implemented is a joint combination strategy, vertical integrity strategy or (forward integrity strategy, backward integrity strategy, and horizontal integrity strategy) intensive strategy (market penetration strategy and product development strategy), as well as diversification strategy implementing related/concentric diversification strategies. If analyzed with Islamic ethics, in this case it is not only focused on general strategies but also in line with things that have been regulated by Islam.